2022
DOI: 10.1002/cphc.202100778
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of PBS/CNTs Nanocomposite Foam for Electromagnetic Interference Shielding

Abstract: In order to reduce the pollutants of environment and electromagnetic waves, environment friendly polymer foams with outstanding electromagnetic interference shielding are imminently required. In this paper, a kind of electromagnetic shielding, biodegradable nanocomposite foam was fabricated by blending poly (butylene succinate) (PBS) with carbon nanotubes (CNTs) followed by foaming with supercritical CO 2 . The crystallization temperature and melting temperature of PBS/ CNTs nanocomposites with 4 wt % of CNTs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…As shown in SEM images, some PIAs encounter difficulty in forming microcellular structures by sCO 2 physical foaming technology. Recent studies have shown that the solubility of supercritical fluids depends on the melt viscoelasticity, crystallinity, and cross-linking density of the polymer material, which affects the foam cell morphology. , For this study, D9C1-F and D7C3-F fail in foaming ability due to their highly linear molecular structure and/or poor viscoelasticity (vide DMA and DSC result). This is related to the crystallinity of the material at low foaming temperatures and the low degree of cross-linking at high foaming temperatures.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As shown in SEM images, some PIAs encounter difficulty in forming microcellular structures by sCO 2 physical foaming technology. Recent studies have shown that the solubility of supercritical fluids depends on the melt viscoelasticity, crystallinity, and cross-linking density of the polymer material, which affects the foam cell morphology. , For this study, D9C1-F and D7C3-F fail in foaming ability due to their highly linear molecular structure and/or poor viscoelasticity (vide DMA and DSC result). This is related to the crystallinity of the material at low foaming temperatures and the low degree of cross-linking at high foaming temperatures.…”
Section: Resultsmentioning
confidence: 93%
“…28,29 Polymer composite foams with conductive fillers (carbon black, carbon nanotubes, graphene, and metal-based particles) are lightweight and have good conductivity especially promising for electromagnetic interference-shielding materials with excellent shielding for electromagnetic radiation. 30,31 The formation of foam cells in the polymer allows the conductive filler to create more conductive channels, and this cellular structure increases the absorption and dissipation of electromagnetic waves. 29 To our best knowledge, only a few studies have been reported on the preparation of sustainable lightweight foams using combinations of CAN polymers and conductive composites.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the MWCNTs content was 4.0 wt %, the EMI shielding effectiveness (SE) value of PBS/MWCNTs nanocomposite reached 26.00 dB. 29 Veluri et al studied the selective localization of MWCNTs and organically modified montmorillonite (O-MMT) in PBS/PLA blends. In PBS/PLA based blends, MWCNTs were predominantly distributed within the PBS phase, while O-MMT was selectively distributed in the PLA phase.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al prepared PBS/MWCNTs composite foam with a percolation threshold of 0.93 wt %. When the MWCNTs content was 4.0 wt %, the EMI shielding effectiveness (SE) value of PBS/MWCNTs nanocomposite reached 26.00 dB 29 . Veluri et al studied the selective localization of MWCNTs and organically modified montmorillonite (O‐MMT) in PBS/PLA blends.…”
Section: Introductionmentioning
confidence: 99%